Influence of Light/Dark Cycles on Body Color, Hepatopancreas Metabolism, and Intestinal Microbiota Homeostasis in Litopenaeus vannamei - Jiao, Lefei; Dai, Tianmeng; Tao, Xinyue; Lu, Jingjing; Zhou, Qicun (Frontiers in Marine Science, 2021)
In aquatic animals, the light/dark cycle acts as an important biological factor that influences the entire life cycle. Until present, evidence regarding the regulation of physiological metabolic process under different light/dark cycles is limited in Litopenaeus vannamei. In this study, we mainly investigated the effects of different light/dark cycles (12 h light/12 h dark, 0 h light/24 h dark) on the hepatopancreas metabolism and intestinal microbiota homeostasis in L. vannamei using multiomics techniques. One interesting finding was that the body color of L. vannamei became darker after dark treatment for 8 weeks. Further hepatopancreas transcriptome analysis identified down-regulated genes involved in regulating nutrition metabolism, body-color formation, diurnal rhythm, immune function, hormone levels, and posttranslational modifications. The intestinal microbiota analysis showed that dark treatment-induced alterations in intestinal bacterial abundances in L. vannamei, such as decreased (P < 0.05) relative abundance of Formosa, Demequina, Lutimonas and increased (P < 0.05) relative abundance of Ruegeria, Vibrio, Actibacter, Roseovarius, Ilumatobacter, and Kriegella at the genus level. The microbiota functional analysis demonstrated that the dark treatment mainly increased susceptibility of pathogens, decreased nutrition metabolism, and influenced circadian rhythm. This study indicated for the first time that constant darkness treatment darkened the body color and altered hepatopancreas metabolism and intestinal microbiota homeostasis in L. vannamei, which might give potential clues for improving the productive capacities by changing light/dark cycles in shrimp farming.